Trophic levels of decomposers in the treatment of herbicide wastewater: a mediator of positive interactions among microbial community assembly, function and stability - Xu, Fei; Wu, Wenjie; Teng, Jun; Wei, Xinyi; Wang, Jinhui; Zhao, Zheng; Liu, Mengyu; Wang, Hao; Kong, Qiang (Frontiers in Microbiology, 2025)
Current wastewater treatment methods tend to acclimate to sludge, but they may not be able to address the presence of herbicides with complex components in agricultural runoff. In this study, we constructed decomposer trophic levels by setting single-channel and multichannel sequencing processes for different herbicide-containing wastewater treatments. Each treatment unit was divided into bacteria-only, wetland plant-only, and wetland plant-microbe continuum treatments. We designed three experiments to investigate the effects of herbicide type, trophic level and biological interaction on system stability, which was predominantly controlled by microbial community assembly processes and functions. The results revealed a threshold for the transition from stochastic to deterministic processes as the concentrations of the herbicides glyphosate (PMG) and atrazine (ATZ) increased. Compared with the effluent water quality of the single herbicide treatment, the decomposer trophic level significantly increased the stochastic effect of the system on effluent water quality. The similarity differences caused by the drift from the parallel units in the primary levels (ca. Dintralevels = 0.22) bridged the gap to the secondary levels (ca. Dintralevels/Dinterlevels = 1.13), which resulted in the best community stability. Analysis of the microbial community life history strategies indicated that multichannel configurations led to a transition in microbial metabolic capacity (RS selection) and environmental responsiveness (RC selection) under herbicide stress to maintain community stability. Therefore, the system stability in the water treatment process could be optimized by the systematic design of the microbial decomposition trophic level, which is considered an important contributor to the positive coordination between biodiversity and function.